Effect of polyhexamethylene biguanide-coated central venous catheters on bacterial colonization in cancer patients undergoing abdominal surgery: a randomized controlled trial - Dong, Jun; Yang, Yong; Li, Qi; Xu, Jia-Xuan; Shen, Yan-Fen; Wang, Hong-Zhi (Frontiers in Medicine, 2025)
BackgroundCentral venous catheters (CVCs) are widely used in critically ill patients, including cancer patients, but are associated with complications such as catheter-related bloodstream infections (CRBSIs). This study evaluates the effectiveness of polyhexamethylene biguanide (PHMB)-coated CVCs in reducing catheter-tip bacterial colonization in cancer patients undergoing abdominal surgery.MethodsA prospective, randomized, monocentric clinical trial was conducted at Peking University Cancer Hospital from March 2017 to April 2019. Surgical cancer patients requiring CVCs were randomized into two groups: a PHMB-coated CVC group (Certofix® protect) and a standard CVC group (Certofix®). The primary outcome was catheter tip bacterial colonization, and the secondary outcomes included catheter retention time and hospital length of stay.ResultsA total of 1,185 patients were included in the analysis. The incidence of catheter tip bacterial colonization was 2.5% in the PHMB-coated group and 4.2% in the standard CVC group (p = 0.10). Hospital length of stay was significantly shorter in the PHMB-coated group (p < 0.001). Subgroup analysis showed reduced bacterial colonization in male patients in the PHMB-coated group (p = 0.04).ConclusionPolyhexamethylene biguanide-coated CVCs did not significantly reduce catheter tip bacterial colonization in the overall population but showed a beneficial effect in male cancer patients undergoing abdominal surgery. In clinical practice, it is necessary to consider various factors when selecting the type of catheter.Clinical trial registrationNo. chiCTR-IPR-16010027.